PPDPF alleviates hepatic steatosis through inhibition of mTOR signaling - Ning Ma (Nature Portfolio, 2021)
Non-alcoholic fatty liver disease (NAFLD) has become a prevalent chronic liver disease, however, drugs to treat this disease are still lacking. Here, the authors show that PPDPF inhibits the development of hepatic steatosis by negatively regulating mTORC1-S6K-SREBP1 signaling, which provides a potential therapeutic candidate for NAFLD treatment.